2018
DOI: 10.1017/s1355617718000140
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction and Depression in Pediatric Temporal Lobe Epilepsy: The Contribution of Hippocampal Sclerosis and Psychosocial Factors

Abstract: The current findings offer strong support for the relationship between executive function (EF) and depression in pediatric TLE. Also, as HS is not modifiable, these findings suggest EF intervention may be a potential modality for improving health-related quality of life (HRQOL) in youth with TLE. (JINS, 2018, 24, 606-616).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…In our study, we found that intrinsic alertness, phasic alertness, mean RT for spatial cues, mean RT for center cues, and executive function were significantly increased when there was no difference in alertness and orientation effect in TLE patients relative to NCs at baseline. In general, these data reveal a potential cognitive decline in TLE patients, which was consistent with several other studies conducted by Schraegle and Nussbaum ( 30 ), Li et al ( 31 ), Nau et al ( 32 ), and van den Berg et al ( 33 ). TLE is associated with decreases in cognitive function, such as attention, memory and language, which may be present in most patients with epilepsy ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that intrinsic alertness, phasic alertness, mean RT for spatial cues, mean RT for center cues, and executive function were significantly increased when there was no difference in alertness and orientation effect in TLE patients relative to NCs at baseline. In general, these data reveal a potential cognitive decline in TLE patients, which was consistent with several other studies conducted by Schraegle and Nussbaum ( 30 ), Li et al ( 31 ), Nau et al ( 32 ), and van den Berg et al ( 33 ). TLE is associated with decreases in cognitive function, such as attention, memory and language, which may be present in most patients with epilepsy ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…A very recent example of successful bringing together the separate camps of neuropsychology and psychopathology is a study of executive functioning and depression in children with temporal lobe epilepsy. 58 Such investigations are yet to be undertaken for children who have undergone epilepsy surgery. Finally, the effects of environmental variables on postsurgical cognitive development are debated and have to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another study reported that children 8-16 years old with temporal lobe epilepsy took a mean of 1.45 antiepileptic drugs. 17 Two other studies found that more than half of children with temporal lobe epilepsy and FLE (56.7%-71.0%) were on antiepileptic drug polytherapy (defined as more than 1 antiepileptic drug). 28,33 In a severe form of the condition, PCDH19-related focal epilepsy, 82% of 2-12-year-old children were on more than 3 antiepileptic drugs.…”
Section: Humanistic Burdenmentioning
confidence: 98%
“…Studies used different instruments to test for language, reading, memory, motor, and visuospatial development delays and found that patients suffer from significant neurologic developmental delays. Instruments included the Delis-Kaplan Executive Function System (DKEFS), 17,26 the California Verbal Learning Test-Children's Version (CVLT-C), 25,17 the Trail Making Tests, 23,26 and the Behavior Rating Inventory of Executive Function (BRIEF). 17,22 Four studies reported on patient IQ, 17,23,22,26 two of which used the Wechsler Intelligence Scale for Children (WISC-IV).…”
Section: Humanistic Burdenmentioning
confidence: 99%
See 1 more Smart Citation